Determinants of Mobile Voluntary Counselling and Testing of HIV Use among Gay in Surakarta, Central Java - Nadia Ayu Irma Nindiyastuti; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2018)
Background: HIV infection remains a major global health problem, especially among bisexuals, men who have sex with men (MSM), and homosexuals. The number of AIDS patients in Indonesia from January to March 2017 was 673 people, the number of HIV infections was 10,376 people, and number of AIDS death was 61 people. The purpose of this study was to analyze the determinants of the use of mobile VCT of HIV in MSM community in Surakarta, Central Java.Subjects and Method: A cross-sectional study was conducted in Surakarta, Central Java, from October to November 2018. A sample of 200 MSM was selected by fixed disease sampling, including 50 MSM who used mobile VCT service and 150 MSM who did not use mobile VCT service. The dependent variable was mobile VCT of HIV use. The independent variables were intention, attitude, cues to action, perceived benefit, perceived barrier, and perceived susceptibility. The data were collected by questionnaire and analyzed by path analysis.Results: Mobile VCT of HIV use was directly and positively affected by intention (b= 1.67; 95% CI= 0.73 to 2.56; p<0.001), attitude (b= 1.47; 95% CI= 0.43 to 2.52; p= 0.006), cues to action (b= 1.22; 95% CI= 0.29 to 2.14; p= 0.009), and perceived benefit (b= 1.99; 95% CI= 1.04 to 2.95; p<0.001). It was negatively affected by perceived barrier (b= -1.58; 95% CI= -2.49 to -0.67; p= 0.001). Mobile VCT use was indirectly affected by cues to action, perceived seriousness, and perceived susceptibility.Conclusion: Mobile VCT of HIV use is directly and positively affected by intention, attitude, cues to action, and perceived benefit, but is negatively affected by perceived barrier.Keywords: mobile VCT use, HIV infection, determinants, men who have sex with men, Health Belief ModelCorrespondence: Nadia Ayu Irma Nindiyastuti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36A, Surakarta, Central Java 57216. Email: nadiaayu21051992@gmail.com.Mobile: 081252097440.Journal of Health Promotion and Behavior (2019), 3(3): 155-165https://doi.org/10.26911/thejhpb.2018.03.03.03